680.BRIDGING THE GAP: QUALITATIVE COMPARATIVE ANALYSIS OF INDUSTRY 4.0 AND INDUSTRY 5.0 - Aleksandar, Argilovski; Ema, Vasileska; Ognen, Tuteski; Boban, Kusigerski; Bojan, Jovanoski; Mite, Tomov (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2024)
The fourth industrial revolution comes with a lot of promises for the future of effective and efficient manufacturing. However, in the light of the rapid change of the technology, smart manufacturing is undergoing trans-formation driven by two distinct paradigms: Industry 4.0 advocates for the shift to-wards digitization and automation, while the emerging Industry 5.0 prioritizes human-centric approaches. Currently, there is a need to consider sustainable development and the crucial role of humans in the assumptions of industry’s future development. Concerns about the implementation of digital technologies became the basis for building the assumptions of Industry 5.0. This article will present a comparative qualitative compassion between Industry 4.0 and Industry 5.0 in order to precisely characterize both concepts.